Introduction to polymers - Young, Robert J; Lovell, Peter A (New York : CRC Press, 2011)
Thoroughly updated, Introduction to Polymers, Third Edition presents the science underpinning the synthesis, characterization and properties of polymers. The material has been completely reorganized and expanded to include important new topics and provide a coherent platform for teaching and learning the fundamental aspects of contemporary polymer science.
Index 653-668p.
Keywords: Electrical properties; Multicomponent polymer systems; Scattering methods; Viscoelasticity; Polyaddition